2013
DOI: 10.17511/ijmrr.2013.i05.11
|View full text |Cite
|
Sign up to set email alerts
|

Blindness: Indian scenario: Is it really preventable?

Abstract: Blindness & visual impairment are important preventable morbidities. It is more important in developing countries like India. Two important aspects are lack of medical care available in peripheral part of country & lack of awareness of general population for medical care. Almost 80-90 % of population is suffering from preventable cause of blindness. There is an urgent need for screening programs & availability of medical care from government & Non government organization in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Falls among visually impaired people can occur due to intrinsic and extrinsic factors [ 15 ]. In developing countries like India, people with visual impairment face different challenges, such as accessibility, navigator barriers, poverty, and healthcare utility challenges [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falls among visually impaired people can occur due to intrinsic and extrinsic factors [ 15 ]. In developing countries like India, people with visual impairment face different challenges, such as accessibility, navigator barriers, poverty, and healthcare utility challenges [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies 9,10 found that positive predictive values of suitability of corneas increased from 38.5% for corneas retrieved from donors aged more than 80 years (where DRT > 6 h and a tissue retrieval-to-reception time >24 h) to 64.7% for those from donors aged less than 80 years (where DRT < 6 h and a tissue retrieval-toreception time <24 h).…”
Section: Discussionmentioning
confidence: 96%
“…The factors that cause inappropriate development of stereopsis are many; one notable cause being uncorrected refractive errors. 8,11,12 All types of refractive errors adversely affect stereopsis by inducing visual blur, resulting in decreased binocular function with low sensory fusion. 8,13 In this study, subnormal stereopsis was found more in simple myopia, followed by compound myopic astigmatism and amblyopia.…”
Section: Discussionmentioning
confidence: 99%